A Comparative Study of Indonesian and Egyptian Islamic Law on Post-Divorce Child Custody Rules - Rauf, Salim; Dulsukmi Kasim; Rizal Darwis (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2025)
This study aims to compare Islamic law in Indonesia and Egypt regarding child custody (hadhanah) regulations after divorce, with a focus on the principles of protection and the best interests of the child. This research employs a library research method, examining sources such as the Qur’an, hadith, classical Islamic jurisprudence texts, statutory regulations, and relevant scholarly studies. The research process involves reading, reviewing, and analyzing literature related to the implementation of hadhanah in both legal systems. The findings indicate that Indonesia views hadhanah as an essential aspect of family Law that emphasizes child protection and welfare. Legally, mothers receive priority in caring for young children; however, final decisions are always made in the child's best interests. This reflects the adaptive, humanistic, and justice-oriented nature of Islamic Law in Indonesia, which remains responsive to modern societal needs. Meanwhile, Egypt places maslahah al-thifl (the child’s best interest) at the core of its regulation of hadhanah and has successfully integrated Islamic values into modern national law. Both countries affirm that the child’s welfare is the paramount consideration in determining custody after divorce.